2005
DOI: 10.1063/1.2060935
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen plasma effects on ultralow-k porous SiCOH dielectrics

Abstract: This study investigated the interactions of hydrogen plasmas with ultralow-k porous SiCOH (pSiCOH) films and their dependency on the values of the original dielectric constant, porogen used for the preparation of films, and substrate temperature during the plasma treatment. pSiCOH films of similar dielectric constants have been prepared by plasma-enhanced chemical-vapor deposition using an identical SiCOH skeleton precursor, but with two different organic porogens. The films exposed to the hydrogen plasmas hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 9 publications
(10 reference statements)
2
33
0
Order By: Relevance
“…For example, the activated silyl sites are generated from breaking Si-C, Si-H, and SiSi bonds by active hydrogen species in the plasma. These are then available to react with oxygen to generate Si-O-Si structures [11]. It is thought that high contents of Si-O bond that has high thermochemical energy [10] in the low-k SiCOH films can contribute to decrease of leakage current pass.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the activated silyl sites are generated from breaking Si-C, Si-H, and SiSi bonds by active hydrogen species in the plasma. These are then available to react with oxygen to generate Si-O-Si structures [11]. It is thought that high contents of Si-O bond that has high thermochemical energy [10] in the low-k SiCOH films can contribute to decrease of leakage current pass.…”
Section: Resultsmentioning
confidence: 99%
“…Some groups report that these plasmas have no effect on the SiOC:H film, 4,19,20,22 others report that it enhances the dielectric properties, 24 and yet others indicate that H 2 plasmas cause significant damage. 3,21 The replacement of CH 3 17,19,20 However, certain additional activation provided, for instance, by ion radiation and UV light makes these reactions possible, causing the difficulty to realize damage-free processes in the reactive ion etching ͑RIE͒ condition. 19,25 For instance, Matshushita et al 19 showed that the damage during the H 2 plasma treatment depends on the type of chamber used.…”
Section: H568mentioning
confidence: 99%
“…The SiOC:H film contains bonds local- ized at 1200 − 1000 cm −1 from C-O-C or Si-O-C asymmetric stretching vibrations. 21 However, the identification is difficult because they overlap with the Si-O-Si asymmetric stretching band. After the NH 3 plasma treatment, a clear shift to higher wavenumbers of the Si-O-Si absorption band is observed.…”
Section: H570mentioning
confidence: 99%
“…For example, hydrogen incorporation is known to decrease dielectric constant, breakdown strength, hardness, refractive index, and increase leakage current, to name a few. [10][11][12] A post-deposition anneal at increased temperatures is a common method to decrease the hydrogen concentration within a PECVD grown film. However, to maintain the integrity of the coating and the possible substrates which can be used, this method is undesirable.…”
Section: Introductionmentioning
confidence: 99%